Subclinical Visuospatial Impairment in Parkinson’s Disease: The Role of Basal Ganglia and Limbic System - Caproni, Stefano; Muti, Marco; Di Renzo, Antonio; Principi, Massimo; Caputo, Nevia; Calabresi, Paolo; Tambasco, Nicola (Frontiers in Neurology, 2014)
BACKGROUND: Visual perception deficits are a recurrent manifestation in Parkinson's disease (PD). Recently, structural abnormalities of fronto-parietal areas and subcortical regions, implicated in visual stimuli analysis, have been observed in PD patients with cognitive decline and visual hallucinations. The aim of the present study was to investigate the salient aspects of visual perception in cognitively unimpaired PD patients. METHODS: Eleven right-handed non-demented right-sided onset PD patients without visuospatial impairment or hallucinations and eleven healthy controls were studied with fMRI while performing a specific visuoperceptual/visuospatial paradigm that allowed to highlight the specific process underlying visuospatial judgment. RESULTS: Significant changes in both cortical areas and subcortical regions involved in visual stimuli processing were observed. In particular, PD patients showed a reduced activation for the right insula, left putamen, bilateral caudate and right hippocampus, as well as an over-activation of the right dorso-lateral prefrontal and of the posterior parietal cortices, particularly in the right hemisphere. CONCLUSIONS: We found that both loss of efficiency and compensatory mechanisms occur in PD patients, providing further insight into the pathophysiological role of the functional alterations of basal ganglia and limbic structures in the impairment of visuoperceptual and visuospatial functions observed in PD.